Non-native writers and the use of appraisal resources in research article introductions - Fitriati, Sri Wuli; Solihah, Yuni Awalaturrohmah (Indonesian Journal of Applied Linguistics, 2019)
Writing an introduction section of a research article usually requires the interpersonal voice and arguments for building up a sense of persuasiveness that will entice readers. A quality research article introduction can be achieved by using appraisal resources to represent the writers’ ideas and propositions effectively. Using twenty introduction sections of research articles written in English by Indonesian and Chinese writers as non-native writers, this study examines the use of appraisal resources and compares their distributions. By employing textual analysis and using Appraisal resources theory drawn from the work of Martin and White (2005), the findings reveal that there are both similarities and differences in the distribution of appraisal resources between Indonesian and Chinese writers in the introduction sections of research articles. In terms of similarities, both Indonesian and Chinese writers use attitude (appreciation), expand (engagement), and force (graduation) as the most used appraisal resources in their writing. What is different, however, is that the Indonesian writers seem more likely than Chinese writers to use appraisal resources overall, except for graduation resources, which were used more often by the Chinese writers. This article discusses some of the pedagogical implications for those who are teaching students of English as a foreign language and want to improve and strengthen their voice and arguments in the writing of research article introductions.